Religion and the Study of Peace: Practice without Reflection - Omer, Atalia ca. 20./21. Jh. (Religions, 2021)
Religion can be good and bad. For too long, the field of religion and peace has repeated this argument, cogently articulated by R. Scott Appleby in his field shaping The Ambivalence of the Sacred. It is time to examine whether there are other arguments to be made. The field of religion and peace is multifaceted and has grown exponentially in recent decades, primarily by enhancing various sites of policy making to mobilize "good" religion more effectively for its utility while devising more complex mechanisms to contain "bad" religion. This is not a bad development in and of itself and many actors populating the religion and peace spaces of practice do a lot of good in the world. However, without also subjecting the field to critique of its basic operative categories of analysis, the field in its various nodes will remain just that: practice, without reflection to recall Paolo Freire’s critical pedagogical approach to transforming the world.